2005
DOI: 10.1136/pgmj.2004.026229
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and follow up of 302 patients with Mycobacterium kansasii pulmonary infection: a 50 year experience

Abstract: Aims: To analyse clinical features and treatment outcomes of patients with pulmonary Mycobacterium kansasii infection treated at Hines VA Hospital between 1952 and 1995, and followed up until 2003. Findings: 302 patients were confirmed to have M kansasii pulmonary infection; diagnosis was not made until death in 2%. The average age was 50 years old; 76% were white; all were men. Productive cough, dyspnoea, and chest pain were common; 16% were asymptomatic. Right sided, apical or subapical, thin walled cavitary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 22 publications
0
38
0
2
Order By: Relevance
“…Underlying lung conditions likely increase susceptibility to infection due to impaired alveolar macrophage phagocytic activity (35) and immune responses (36). However, the lack of association between underlying lung disease alone and disseminated M. kansasii disease (34) suggests that extrapulmonary immune responses largely remain intact in these patients. Conversely, the history of smoking in the majority of GATA2-deficient patients with disseminated disease suggests that in the setting of primary immune defects, extensive tobacco exposure may increase the risk for M. kansasii dissemination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underlying lung conditions likely increase susceptibility to infection due to impaired alveolar macrophage phagocytic activity (35) and immune responses (36). However, the lack of association between underlying lung disease alone and disseminated M. kansasii disease (34) suggests that extrapulmonary immune responses largely remain intact in these patients. Conversely, the history of smoking in the majority of GATA2-deficient patients with disseminated disease suggests that in the setting of primary immune defects, extensive tobacco exposure may increase the risk for M. kansasii dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…Preexisting lung disease (e.g., heavy smoking, chronic obstructive pulmonary disease) is the most prevalent underlying condition among patients with pulmonary M. kansasii infections (34). Underlying lung conditions likely increase susceptibility to infection due to impaired alveolar macrophage phagocytic activity (35) and immune responses (36).…”
Section: Discussionmentioning
confidence: 99%
“…Since the prevalence of pulmonary NTM infections, especially MAC, is on the rise, the likelihood of encountering patients with these infections and concurrent lung cancer may increase. Although a causal association between lung cancer and pulmonary NTM infection is not clear, the high prevalence of lung cancer lesions at old M. kansasii sites suggested the possibility of scar tumor, similar to those after pulmonary tuberculosis [7].…”
Section: Discussionmentioning
confidence: 99%
“…A study at a single institution in Japan reported that lung cancer coexisted in 1.8% of the patients with pulmonary NTM (including 660 MAC, 126 M. kansasii, and 19 M. fortuitum) infection [6]. The figure for a series of 302 patients with M. kansasii infection was 6%, and most of these were male smokers [7]. Since the prevalence of pulmonary NTM infections, especially MAC, is on the rise, the likelihood of encountering patients with these infections and concurrent lung cancer may increase.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of M. kansasii among the causative microorganisms of pulmonary NTM disease has been reported as 8.1% in Japan, and it has increased in Japan and the United States of America [8] [9].…”
Section: Discussionmentioning
confidence: 99%